Analysis of radiopacity, pH and cytotoxicity of a new bioceramic material - Letícia Chaves de SOUZA; Mamatha YADLAPATI; Samuel O DORN; Renato SILVA; Ariadne LETRA (University of São Paulo, 2015)
AbstractObjective RetroMTA® is a new hydraulic bioceramic indicated for pulp capping, perforations or root resorption repair, apexification and apical surgery. The aim of this study was to compare the radiopacity, pH variation and cytotoxicity of this material to ProRoot® MTA.Material and Methods Mixed cements were exposed to a digital x-ray along with an aluminum stepwedge for the radiopacity assay. pH values were verified after incubation period of 3, 24, 48, 72 and 168 hours. The cytotoxicity of each cement was tested on human periodontal ligament fibroblasts using a multiparametric assay. Data analysis was performed using ANOVA and Tukey'spost hoc in GraphPad Prism.Results ProRoot® MTA had higher radiopacity than RetroMTA®(p<0.001). No significant differences were observed for the pH of the materials throughout experimental periods (p>0.05) although pH levels of both materials reduced over time. Both ProRoot® MTA and RetroMTA® allowed for significantly higher cell viability when compared with the positive control (p<0.001). No statistical difference was observed between ProRoot® MTA and RetroMTA® cytotoxicity level in all test parameters, except for the ProRoot® MTA 48-hour extract media in the NR assay (p<0.05).Conclusion The current study provides new data about the physicochemical and biological properties of Retro® MTA concerning radiopacity, pH and cytotoxic effects on human periodontal ligaments cells. Based on our findings, RetroMTA® meets the radiopacity requirements standardized by ANSI/ADA number 572, and similar pH values and biocompatibility to ProRoot® MTA. Further studies should be performed to evaluate additional properties of this new material.